Contemporary Trends in Accounting, Finance and Financial Institutions Proceedings from the International Conference on Accounting, Finance and Financial Institutions (ICAFFI), Poznan 2016 (Springer Proceedings in Business and Economics,, 2018)
This book gathers the proceedings of the ICAFFI International Conference on Accounting, Finance and Financial Institutions. The main topics addressed include: corporate finance, financial markets and asset pricing, empirical finance, taxation, financial risk management, international finance, financial econometrics, financial reporting and accounting standards, managerial accounting, measuring financial performance, accounting information systems, and current issues in accounting and finance in emerging and other markets. Presenting both cutting-edge research and a broad set of methods, and combining practical and theoretical perspectives, the book offers a valuable resource for researchers, practitioners and regulators alike.